A Comprehensive Guide for Assessing Covalent Inhibition in Enzymatic Assays Illustrated with Kinetic Simulations. Issue 6 (7th June 2022) - Mons, Elma; Roet, Sander; Kim, Robbert Q.; Mulder, Monique P. C.
Abstract: Covalent inhibition has become more accepted in the past two decades, as illustrated by the clinical approval of several irreversible inhibitors designed to covalently modify their target. Elucidation of the structure‐activity relationship and potency of such inhibitors requires a detailed kinetic evaluation. Here, we elucidate the relationship between the experimental read‐out and the underlying inhibitor binding kinetics. Interactive kinetic simulation scripts are employed to highlight the effects of in vitro enzyme activity assay conditions and inhibitor binding mode, thereby showcasing which assumptions and corrections are crucial. Four stepwise protocols to assess the biochemical potency of (ir)reversible covalent enzyme inhibitors targeting a nucleophilic active site residue are included, with accompanying data analysis tailored to the covalent binding mode. Together, this will serve as a guide to make an educated decision regarding the most suitable method to assess covalent inhibition potency. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol I : Progress curve analysis of substrate association competition Basic Data Analysis Protocol 1A : Two‐step irreversible covalent inhibition Basic Data Analysis Protocol 1B : One‐step irreversible covalent inhibition Basic Data Analysis Protocol 1C : Two‐step reversible covalent inhibition Basic Data Analysis Protocol 1D : Two‐step irreversible covalent inhibition with substrate depletion Basic Protocol II : Incubation time–dependent potency IC50 ( t ) Basic Data Analysis Protocol 2 : Two‐step irreversible covalent inhibition Basic Protocol III : Preincubation time–dependent inhibition without dilution Basic Data Analysis Protocol 3 : Preincubation time–dependent inhibition without dilution Basic Data Analysis Protocol 3Ai : Two‐step irreversible covalent inhibition Alternative Data Analysis Protocol 3Aii : Two‐step irreversible covalent inhibition Basic Data Analysis Protocol 3Bi : One‐step irreversible covalent inhibition Alternative Data Analysis Protocol 3Bii : One‐step irreversible covalent inhibition Basic Data Analysis Protocol 3C : Two‐step reversible covalent inhibition Basic Protocol IV : Preincubation time–dependent inhibition with dilution/competition Basic Data Analysis Protocol 4 : Preincubation time–dependent inhibition with dilution Basic Data Analysis Protocol 4Ai : Two‐step irreversible covalent inhibition Alternative Data Analysis Protocol 4Aii : Two‐step irreversible covalent inhibition Basic Data Analysis Protocol 4Bi : One‐step irreversible covalent inhibition Alternative Data Analysis Protocol 4Bii : One‐step irreversible covalent inhibition